A Rasch analysis of the self-administered Foot Health Assessment Instrument (S-FHAI) - Stolt Minna; Kottorp Anders; Suhonen Riitta (BioMed Central Ltd, 2022)
Background
Reliable and valid measurement is the foundation of evidence-based practice. The self-administered Foot Health Assessment Instrument (S-FHAI) was recently developed to measure patients’ evaluations of their own foot health. Evidence regarding the psychometric properties of the S-FHAI is limited. The aim of this study was to investigate those properties by using a Rasch analysis.
Methods
This methodological study analysed secondary data that was collected from nurses (n = 411) in 2015. The psychometric properties of the S-FHAI were evaluated using the Rasch model. Unidimensionality was analysed first, followed by item functioning, person misfit and differential item functioning (DIF).
Results
The S-FHAI demonstrated evidence of unidimensionality, with an acceptable item fit according to the Rasch model. Person fit and person separation were low, however, indicating restricted separation among different respondents. Item separation was high, demonstrating clear discrimination between the items. No DIF was detected in relation to gender, but significant DIF was demonstrated in relation to age for 6 of the 25 items.
Conclusions
The S-FHAI has potential for use in investigating self-reported foot health. The Rasch analysis revealed that the psychometric properties of the instrument were acceptable, although some issues should be addressed to improve the scale. In future, it may be beneficial to analyse the sensitivity of the items and to test the S-FHAI in more diverse patient populations.